HUBUNGAN PENGETAHUAN KESEHATAN DAN KESELAMATAN KERJA BAGI PETUGAS PENGANGKUT SAMPAH TERHADAP RISIKO DERMATITIS KONTAK - Gustia Padila; Herlina Herlina; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Contact dermatitis is a skin inflammation resulting from contact with exposure, which is toxis or allergic and cause itching, redness, bulge filled the water and swollen. This research aimed to determine correlation of health and safety knowledge to waste transportation officer to the risk of contact dermatitis. This research descriptive correlation cross sectional design. This research was conducted in Workshop Agency of Environment and Sanitation of Pekanbaru involving 62 respondents. The sampling method was simple random sampling. Measuring instrument used was a questionnaire that has been tested for validity and reliability. The analysis used were univariate and bivariate by kolmogorov-smirnov. The result analysis univariate showed that the majority of respondents are in the category of middle adult (54,8%), 29 respondents had junior high education (46,8%), 28 respondents got the information from television (45,2%), 62 respondents has worked more than one year (100%), and 59 respondents had skin problem (95,2%). The result of this research showed that there was no significant correlation between the health and safety knowledge for waste transportation officer to the risk of contact dermatitis p value= 0,821. It is recomended that the Health Agency in providing counseling for waste transportation officer to take care of personal hygiene and the use of personal protective equipment while doing their job avoid being affected by illness which can be caused by garbage.Keywords: Contact dermatitis, health and safety, knowledge